Problems in the educational process during the pediatric surgery area teaching of fourth year medicine students - Sergio Luis González López; Zoe Quintero Delgado; Guillermo Cortiza Orbe; Berta E. Fonseca Romero; Carlos A. Cabrera Machado; Yordan Ponce Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Very typical situations of the Pediatric Surgery Services in the Pediatric Hospital of Cienfuegos may interfere with the appropriate development of the educational process. Consequently, students might not master the principles of medical practice in the most common surgical diseases in children, thus limiting its further application in their professional performances as basic general practitioners. To obtain more accurate information on the causes of this phenomenon is considered to be paramount in order to search for practical solutions to improve the educational process and to fulfil the goals of the teaching stage. The contents on the following information sources are analyzed in this paper: documents for higher education and for medicine career, publications and papers presented in scientific events (directly or indirectly related to the practice of Pediatric Surgery) and hospital statistics. This review was aimed at analyzing the situations that negatively affect the educational process during the pediatric surgery area teaching of fourth year medicine students.